Mechanisms of sampling interstitial fluid from skin using a microneedle patch - Samant, Pradnya P.; Prausnitz, Mark R. (Proceedings of the National Academy of Sciences - PNAS, 2018)
Although interstitial fluid (ISF) contains biomarkers of physiological significance and medical interest, sampling of ISF for clinical applications has made limited impact due to a lack of simple, clinically useful techniques that collect more than nanoliter volumes of ISF. This study describes experimental and theoretical analysis of ISF transport from skin using microneedle (MN) patches and demonstrates collection of >1 μL of ISF within 20 min in pig cadaver skin and living human subjects using an optimized system. MN patches containing arrays of submillimeter solid, porous, or hollow needles were used to penetrate superficial skin layers and access ISF through micropores (μpores) formed upon insertion. Experimental studies in pig skin found that ISF collection depended on transport mechanism according to the rank order diffusion < capillary action < osmosis < pressure-driven convection, under the conditions studied. These findings were in agreement with independent theoretical modeling that considered transport within skin, across the interface between skin and μpores, and within μpores to the skin surface. This analysis indicated that the rate-limiting step for ISF sampling is transport through the dermis. Based on these studies and other considerations like safety and convenience for future clinical use, we designed an MN patch prototype to sample ISF using suction as the driving force. Using this approach, we collected ISF from human volunteers and identified the presence of biomarkers in the collected ISF. In this way, sampling ISF from skin using an MN patch could enable collection of ISF for use in research and medicine.